Migrants from marginal dry areas in Syria: Destinations, employment, and returns - Malika Abdelali-Martini; Kindah Ibrahim; Boubaker Dhehibi (IZA Journal of Migration, 2016)
We examine the determinants of migrants' choices of destination, employment, and remittances from one of the poorest marginal dry areas in Syria. Qualitative and econometric analysis of cross-sectional data indicates that migrants' choices depend mainly on individual, household, and community characteristics and also on availability of opportunities. The main factors affecting the choice of destination and employment are the sending area, age, and sex of migrants, while the educational level had no significant effect in both cases. The larger the endowments of migrants' households, the higher the remittances sent back home to preserve households' assets in marginal dry areas.
Keywords: 330; Syria; Dry areas; Migration; Remittances; Migrants'characteristics; Destination choice; Employment; Gender